2013
DOI: 10.2807/1560-7917.es2013.18.49.20650
|View full text |Cite
|
Sign up to set email alerts
|

A Shigella sonnei outbreak traced to imported basil – the importance of good typing tools and produce traceability systems, Norway, 2011

Abstract: sonnei outbreak traced to imported basil-the importance of good typing tools and produce traceability systems,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…Shared response guidelines [42,50] Structures frequently included policies/protocols [59,60] Reporting -Management protocol -Task Management -Response Plan -Communications/ communication strategy [34,61] Infection planning, control and traceback procedures [62] Systems Reporting, laboratory systems [59] Surveillance systems [41,58,59] Planning; Iterative Improvement of systems [46,48,60] Information management system/ database [41,48,63,64] Information Sharing (data available and useful) [45,48]) Tool sharing during response [65] Lab systems in place [59] Online system for HR recruitment [45] Intentional multidisciplinary engagement, collaborative capacity [43,48,66,67] Standard operating procedures [55] Interoperability [42] Needs assessment and prioritization [38,48] Culture Leadership, accountability, ownership, trust, transparency of processes, systems based thinking, cultural awareness and engagement Leadership to support the iterative and developmental review of collaborative processes [58] Strong, engaged Leadership [32,35,52,68] Accountability; Ownership [67,68] Cultural Engagement; Engagement; Diversity/ Involvement of community [67,…”
Section: Organizational Factors (Applicable To Both Starting Conditiomentioning
confidence: 99%
See 1 more Smart Citation
“…Shared response guidelines [42,50] Structures frequently included policies/protocols [59,60] Reporting -Management protocol -Task Management -Response Plan -Communications/ communication strategy [34,61] Infection planning, control and traceback procedures [62] Systems Reporting, laboratory systems [59] Surveillance systems [41,58,59] Planning; Iterative Improvement of systems [46,48,60] Information management system/ database [41,48,63,64] Information Sharing (data available and useful) [45,48]) Tool sharing during response [65] Lab systems in place [59] Online system for HR recruitment [45] Intentional multidisciplinary engagement, collaborative capacity [43,48,66,67] Standard operating procedures [55] Interoperability [42] Needs assessment and prioritization [38,48] Culture Leadership, accountability, ownership, trust, transparency of processes, systems based thinking, cultural awareness and engagement Leadership to support the iterative and developmental review of collaborative processes [58] Strong, engaged Leadership [32,35,52,68] Accountability; Ownership [67,68] Cultural Engagement; Engagement; Diversity/ Involvement of community [67,…”
Section: Organizational Factors (Applicable To Both Starting Conditiomentioning
confidence: 99%
“…Policies and protocols reported to be supportive included technical guidelines and standard operating procedures, as well as management, response and communication strategies and protocols [34,42,50,59,60,62]. In addition, organizations reported the need for functional systems for information and resource management and sharing and reporting both surveillance and laboratory results [41,43,45,48,55,59,63,64,66,67]. These systems were reported to benefit from being adaptive, flexible/reflexive and improved through iterative feedback and monitoring and evaluation [38,46,48,60].…”
Section: Collaborative Success Factors Categorized As Starting Conditmentioning
confidence: 99%
“…Furthermore, several other studies have reported Shigella associated diarrhea in children living in areas with poor resources [7][8][9]. In developed countries, Shigella have been isolated especially during outbreaks of gastroenteritis following ingestion of contaminated food or water [10,11]. dysenteriae 1 accounts for devastating epidemics [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Salmonella has been isolated from fresh herbs and leafy greens (2), and outbreaks have been associated with the consumption of fresh cilantro (3), fresh parsley (18), and fresh basil in the United Kingdom (8,25) and Denmark (24). In October 2011, there were two related outbreaks of infection caused by Shigella sonnei in Norway associated with pesto made from fresh basil imported from Israel via The Netherlands (12). There is very little information about the fresh basil market because it is assumed that fresh basil is used quickly and consumed locally (27).…”
mentioning
confidence: 98%